A method for producing an indium-tin alloy
Patent Information
- Application Number
- CN202610763741.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-29
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明要解决的主要技术问题是针对现有ITO 溅射料中Al2O3包覆金属液滴,导致金属无法聚集,产品收率低等不足,提供一种铟锡合金的制备方法
本发明采用“煅烧分离-碳热还原” 两步法工艺,先基于ITO溅射废料中不同组分的热稳定性差异:In2O3在1100℃以上、SnO2在1000℃以上可发生明显热分解并挥发,而主要杂质Al2O3在常压下沸点高于2000℃,在工艺温度下保持固态。通过高温煅烧使In2O3和SnO2选择性挥发,同时控制氧分压,实现In2O3、SnO2与Al2O3等杂质的高效分离。然后收集挥发产物后进行还原,将氧化物还原为金属铟和锡,得到高纯度的铟锡合金。
Smart Images

Figure CN122979627A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of indium-tin alloy preparation technology using ITO sputtering materials, and more specifically, to a method for preparing indium-tin alloys. Background Technology
[0002] Indium, a precious and rare metal, is a key raw material for strategic emerging industries and is widely used in the manufacture of ITO sputtering targets. Due to the scarcity of natural indium ore resources and mining restrictions in most countries, recovering indium from indium-containing waste has become the main supply channel. ITO sputtering waste, due to its large market volume and low price, has become a key raw material for indium recovery; however, this waste contains a large amount of Al2O3 and impurities such as Zn and Cu, making recovery difficult.
[0003] Currently, the main methods for separating alloys in ITO sputtering materials include precipitation separation, centrifugal separation, and carbothermal reduction. Precipitation separation achieves separation by reacting a chemical precipitant with metal ions in the waste. However, for ITO sputtering waste with complex composition and high impurity content, precipitation easily introduces new chemical impurities and has poor selective enrichment of indium, limiting its applicability. Centrifugal separation uses centrifugal force to separate different phases in the melt, but it has extremely high requirements for equipment and control, consumes a lot of energy, and is not ideal for separating fine-particle-size Al2O3 impurities. Carbothermal reduction involves mixing ITO sputtering waste with carbon powder and then directly reducing it at 1150-1300℃. Although this method can reduce In2O3 and SnO2, it has problems such as low batch processing capacity, low indium-tin recovery rate, and low product purity. In particular, when the waste contains Al2O3 impurities, the large amount of Al2O3 impurities will coat the generated liquid In-Sn alloy particles at the reduction temperature, making it difficult for the metal to polymerize and resulting in low product purity.
[0004] CN114231743B discloses a method for preparing indium-tin alloy from high-temperature reduction ITO sputtering material, which uses specific slag-forming agents (quartz sand, lime, and alumina) to directly slag and melt ITO sputtering material particles after crushing the blocky ITO sputtering material. During the slag-forming and melting process, the density of the low-melting-point slag layer formed is smaller than that of the indium-tin alloy and the ITO sputtering material, and it can cover the top layer. This not only prevents the smoke and dust from overflowing during the melting process and ensures a more uniform reducing atmosphere in the furnace, but also improves the reaction rate and uniformity of the reducing gas CO formed by the reducing agent with indium-tin oxide. Moreover, this slag system can better capture impurities in the material, thereby ensuring high alloy purity, and it is easier to separate from the alloy melt, thus reducing the amount of alloy entrained in the slag, thereby ensuring a higher direct alloy recovery rate. This patent has the advantage of high production volume, which can ensure that the direct recovery rate of indium tin alloy is as high as 92% or more when the processing volume is large, and the purity of the indium tin alloy is as high as 99% or more. However, it still fails to solve the problem that Al2O3 impurities will coat the liquid In-Sn alloy particles generated at the reduction temperature, resulting in poor separation effect and low purity of indium tin alloy. Summary of the Invention
[0005] The main technical problem to be solved by the present invention is to address the shortcomings of existing ITO sputtering materials, such as Al2O3 coating of metal droplets, which prevents metal from agglomerating and results in low product yield. The present invention provides a method for preparing indium-tin alloy.
[0006] The objective of this invention is achieved through the following technical solution: A method for preparing an indium-tin alloy, comprising the following steps: S1. Crush the ITO sputtering material into powder and dry it; S2. Lay the dried ITO sputtering material in a ceramic boat, and under vacuum or protective gas atmosphere, control the oxygen partial pressure to 10-15 Pa to 10-10 Pa, and heat to 1200℃ to 1300℃ and hold for 2 to 9 hours. S3. Cool to room temperature, collect the condensed In2O3 and SnO2 powders, add a reducing agent to the In2O3 and SnO2 powders, heat to reduce, and obtain In-Sn alloy.
[0007] Furthermore, the ITO sputtering material also includes pretreatment, which includes magnetic separation and manual screening to remove magnetic materials such as iron powder and impurities, thereby reducing the doping of impurities.
[0008] Furthermore, the particle size of the powder is no greater than 74 μm.
[0009] Furthermore, the drying temperature is 100℃~300℃, and the time is 6-8h.
[0010] Furthermore, the ITO sputtering material is laid with a thickness of 0.5~1cm.
[0011] Furthermore, the heating process employs a two-stage heating method: the first stage involves raising the temperature to 800°C at a heating rate of 10°C / min, and the second stage involves raising the temperature from 800°C to 1200~1300°C at a heating rate of 5°C / min.
[0012] Furthermore, the reducing agent is activated carbon.
[0013] Furthermore, the reducing agent has a particle size of 53~74μm.
[0014] Furthermore, the amount of reducing agent added is 10-16% of the mass of In2O3 and SnO2 powders.
[0015] Furthermore, the reduction temperature is 1000~1300℃, and the reduction time is 2-12h.
[0016] Furthermore, the In-Sn alloy also includes vacuum distillation purification to remove other trace impurities from the molten metal.
[0017] Compared with existing technologies, the beneficial effects are: This invention employs a two-step process of "calcination separation-carbothermic reduction." First, it leverages the differences in thermal stability among different components in ITO sputtering waste: In₂O₃ undergoes significant thermal decomposition and volatilization above 1100℃ and SnO₂ above 1000℃, while the main impurity, Al₂O₃, has a boiling point above 2000℃ at atmospheric pressure and remains solid at the process temperature. High-temperature calcination selectively volatilizes In₂O₃ and SnO₂ while controlling the oxygen partial pressure, achieving efficient separation of impurities such as In₂O₃, SnO₂, and Al₂O₃. Then, the volatilized products are collected and reduced to metallic indium and tin, yielding a high-purity indium-tin alloy. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the volatilization rate under different temperatures and times in Example 2; Figure 2 (a) Before and after reduction of ITO sputtering material; (b) During the reduction of ITO sputtering material; (c) In-Sn binary phase diagram; Figure 3 The images show (a) ITO sputtering material before reduction and (b) ITO sputtering material after reduction during the calcination and reduction process. Figure 4The elemental distribution of In-Sn alloy at different reduction stages: (a) Surface of spherical In-Tin alloy during reduction; (b) Cross-section of spherical In-Tin alloy during reduction; (c) Surface of bulk In-Tin alloy during reduction; (d) Cross-section of bulk In-Tin alloy during reduction; (e) In-Tin alloy after reduction. Figure 5 XRF morphology images: (a) residue; (b) volatiles; (c) metal surface after volatiles reduction. Figure 6 Elemental analysis of raw materials and reduced ITO sputtering material: (a) white residual powder; (b) white residual powder after reduction; (e) volatiles; (f) metal after volatile reduction; (g) surface diagram of metal after volatile reduction; Figure 7 Morphology of the reduced raw material and the reduced material after sputtering: (a) white residual powder; (b) white residual powder after reduction; (c) volatiles; (d) metal after reduction of volatiles; Figure 8 The following are elemental analysis diagrams of the calcination residue and the evaporated product: (a) white residual powder; (b) volatile matter. Figure 9 Elemental analysis of the calcination residue and evaporated material after reduction: (a) white residual powder after reduction; (b) metal after reduction of volatiles; (c) surface diagram of metal after reduction of volatiles. Detailed Implementation
[0019] The following examples further explain and clarify the invention, but the specific examples do not limit the invention in any way.
[0020] Example 1 This embodiment provides a method for preparing an indium-tin alloy, the steps of which include: S1. The ITO sputtering material is pretreated by manual screening and mechanical magnetic separation to remove organic plastics and magnetic materials such as iron that can be distinguished by the naked eye.
[0021] S2. The pretreated ITO sputtering material is pulverized to a particle size of no more than 74 μm, and then dried at 200 °C for 6 hours to fully remove adsorbed moisture.
[0022] S3. Spread the dried ITO sputtering material evenly in the ceramic boat, controlling the material layer thickness to be approximately 0.5 mm. Push the ceramic boat into the constant temperature zone of the tube furnace, seal it, and continuously purge with nitrogen as a protective atmosphere at a flow rate of 50 mL / min, controlling the oxygen partial pressure to 10. -10 Pa. First, the temperature is increased to 800℃ at a heating rate of 10℃ / min, then increased to 1250℃ at a heating rate of 5℃ / min, and held at this temperature for 6 hours. At this temperature, In2O3 and SnO2 undergo thermal decomposition and volatilization.
[0023] S4. After calcination, the furnace is cooled to room temperature, and the volatile powder in the condensation zone is collected. The collected volatiles are mixed with activated carbon powder at a mass ratio of 100:8. The mixture is then loaded into a ceramic boat and placed in a tube furnace under nitrogen protection. The temperature is increased to 1300℃ at 10℃ / min and held for 3 hours to fully reduce In₂O₃ and other oxides to liquid metal. After the reaction is complete, the mixture is cooled to room temperature to obtain the In-Sn alloy.
[0024] Example 2 This embodiment provides a method for preparing an indium-tin alloy, the process of which is the same as in Embodiment 1, the difference being that different calcination temperatures and times are set in this embodiment. Specifically, calcination is carried out at 1200℃ for 6h, 7h, 8h, and 9h respectively; at 1250℃ for 4h, 5h, 6h, and 7h respectively; and at 1300℃ for 2h, 3h, and 4h respectively. The volatilization rate is then measured as follows. Figure 1 As shown.
[0025] In the above embodiments, the material layer thickness is controlled to be 1 mm, and the oxygen partial pressure is controlled to be 10. -15 The preparation of indium-tin alloy in ITO sputtering material can be completed by adding 10-16% of reducing agent, reducing at 1000-1300℃ for 2-12 hours.
[0026] Example 3 This embodiment provides a method for preparing an indium-tin alloy, the steps of which include: S1. The ITO sputtering material is pretreated by manual screening and mechanical magnetic separation to remove organic plastics and magnetic materials such as iron that can be distinguished by the naked eye.
[0027] S2. The pretreated ITO sputtering material is pulverized to a particle size of 53-74 μm, and then dried at 200°C for 6 hours to fully remove adsorbed moisture.
[0028] S3. Spread the dried ITO sputtering material evenly in the ceramic boat, controlling the material layer thickness to be approximately 0.5 mm. Push the ceramic boat into the constant temperature zone of the tube furnace, seal it, and continuously purge with nitrogen as a protective atmosphere at a flow rate of 50 mL / min, controlling the oxygen partial pressure to 10. -10 Pa. First, the temperature is increased to 800℃ at a heating rate of 10℃ / min, then increased to 1250℃ at a heating rate of 5℃ / min, and held at this temperature for 6 hours. At this temperature, In2O3 and SnO2 undergo thermal decomposition and volatilization.
[0029] S4. After calcination, the furnace is cooled to room temperature, and the volatile powder in the condensation zone is collected. The collected volatiles are mixed with activated carbon powder at a mass ratio of 10:1. The mixture is then loaded into a ceramic boat and placed in a tube furnace under nitrogen protection. The temperature is increased to 1300℃ at 10℃ / min and held for 2 hours to fully reduce In₂O₃ and other oxides to liquid metal. After the reaction is complete, the mixture is cooled to room temperature to obtain the In-Sn alloy.
[0030] The composition of ITO sputtering material during the calcination and reduction processes is analyzed in detail below:
[0031] Phase analysis results of ITO sputtering material before and after reduction are as follows: Figure 2 As shown in (a), by comparing the XRD patterns of ITO sputtered powder and the mixed powder of ITO sputtered powder and activated carbon, it can be seen that the ITO sputtered powder is mainly composed of SnO2 and In2O3, while the mixed powder, in addition to the original oxides, also shows characteristic diffraction peaks of carbon, indicating that carbon has been successfully introduced into the system as a reducing agent. The surface of the In-Sn alloy obtained after reduction mainly exhibits the pure indium (In) phase. According to the In-Sn binary alloy phase diagram, when the mass fraction of tin is less than 10 wt.%, the In-Sn alloy will exhibit a single In phase, because a small amount of Sn has dissolved in In and therefore does not show an independent phase in the XRD. Therefore, to further clarify the composition, it is necessary to combine elemental analysis methods to obtain the mass fraction distribution of each element.
[0032] The phase evolution of the sample at different stages during the reduction process is as follows: Figure 2 As shown in (b). Compared with the phase diagrams before and after reduction, the XRD diffraction peaks of the sample during reduction are more dispersed and the main peak intensity is lower. This is because the spherical In-Sn alloy particles are too small compared to the bulk phase analysis sample and too large compared to the powder phase analysis sample, making it difficult to accurately detect their phases. Therefore, the peaks of the relatively flat and larger bulk In-Sn alloy cross-section are more obvious than those of the spherical In-Sn alloy. However, due to the excessive impurities in the bulk In-Sn alloy during reduction, the phase peak intensity is also weaker compared to before and after reduction. Furthermore, the surface of the bulk In-Sn alloy has too many undulations and too many impurities, making phase analysis difficult.
[0033] like Figure 3The residue of the calcined ITO sputtering material was mainly composed of Al2O3, indicating that In2O3 and SnO2 had been essentially thermally decomposed and completely volatilized during the high-temperature calcination process. In contrast, obvious In2O3 and SnO2 diffraction peaks were detected in the volatiles after calcination, and their phase characteristics were consistent with those of the original ITO sputtering material powder, indicating that In2O3 and SnO2 migrated to the condensation zone in a volatilized form during calcination, and their proportions were basically consistent with those of the ITO target material.
[0034] like Figure 4 As shown in (a), the mass fraction of In is 64.78 wt.%, Sn is 0 wt.%, C is 11.05 wt.%, and O is 24.17 wt.%, while the element distribution in the cross-section of the spherical In-Sn alloy is as follows: Figure 3 As shown in (b), the mass fractions of In are 56.74 wt.%, Sn is 3.84 wt.%, C is 24.35 wt.%, and O is 15.07 wt.%. This is lower than the theoretically complete reduction of In-Sn ratio, while the carbon mass fraction is higher. This is because elements contained in the resin used for fixation were also detected during elemental analysis. Figure 4 (b) The color intensity of each element in the small balls and the area they occupy indicate that the element mass fraction of each ball is basically consistent, therefore, [the appropriate method is to select this method]. Figure 4 (b1) represents the elemental composition of the spherical In-Sn alloy cross-section, where the mass fraction of In is 80.26 wt.%, Sn is 5.69 wt.%, C is 8.18 wt.%, and O is 5.87 wt.%. This indicates that the internal reaction of the spherical In-Sn alloy is basically complete. The difference in elemental composition between the spherical In-Sn surface and the cross-section is mainly due to the fact that as the reaction temperature increases, the ITO sputtering powder is reduced to liquid In-Sn alloy. Under the influence of liquid surface tension, the liquid In-Sn alloy shrinks into spherical droplets. During this process, because the C powder and ITO sputtering powder have low density, they easily float on the surface of the alloy liquid and are fixed to the spherical alloy surface during cooling and solidification, resulting in a higher mass fraction of C and O on the surface of the spherical In-Sn alloy.
[0035] The In-Sn alloying elements at different reduction stages are shown in Table 1 below: Table 1
[0036] To further characterize the elemental composition of the residues, volatiles, and the metals after volatile reduction in greater detail, XRF fluorescence analysis was used for detection. Figure 5 As shown, the morphology of the residue is as follows: Figure 5 As shown in (a), the residual powder is mainly grayish-white, with some larger particles, and is generally loose. The morphology of the volatiles is as follows: Figure 5 As shown in (b), the volatile powder is jet black, and the powder exhibits better polymerizability compared to the residue. The metal after reduction of the volatile powder is as follows: Figure 5 As shown in (c), the metal surface exhibits a distinct metallic luster, and to meet the size requirements of XRF for bulk samples, the metal block was extruded into a sheet shape through a plastic film. XRF elemental analysis is shown in Table 2 below: Table 2
[0037] like Figure 6 The calcined evaporate exhibits a distinct crystalline morphology, with smaller particles mostly displaying a needle-like structure, while some larger particles reach a diameter of 100 μm, and their surfaces are covered with a small amount of powder. The metal morphology formed after carbothermic reduction of the evaporate is relatively smooth, with no obvious impurities. Further observation of the metal surface reveals a significant difference between its external and internal morphologies: the surface contains sparsely distributed white and black particles, which are extremely small in size and distributed in a dotted pattern. Elemental analysis of the ITO sputtering material is shown in Table 3 below. Table 3
[0038] As shown in 7(a), the residual powder after calcination has a small particle size and good dispersibility. Some of the agglomerated particles consist of a large number of fine powder particles approximately 1 μm in size, exhibiting diverse morphologies. In contrast, the residual powder after reduction... Figure 7 (b) A small number of scattered small spherical particles were observed. This may be because the residue after calcination still contained a very small amount of In₂O₃, which was reduced and agglomerated into larger metal spheres during the subsequent reduction process; or it may be that during the calcination stage, In₂O₃ was partially reduced in a reducing atmosphere and remained in the residue to form an In–Sn alloy. Therefore, the maximum volatilization rate decreased with decreasing calcination temperature. Thus, re-sieving the reduced residue powder and re-calcining the large agglomerates can help further improve the recovery rate of indium.
[0039] The elemental analysis of the residue after calcination is shown in Figure 8(a). Spot 1# is fine powder with an oxygen content of 45.11 wt.% and an Al content of 53.22 wt.%, confirming that these small powder particles are Al₂O₃ particles. Spots 2# and 3# have extremely low Al content, with O content decreasing to around 11 wt.%, while In content increases to over 70 wt.%, indicating the presence of some In-Sn alloy microspheres during calcination. The volatiles after calcination are shown in Figure 8(a). Figure 8As shown in (b), although there are slight differences in morphology among #4, #5, and #6, their elemental contents are basically the same, indicating that the volatiles are high-purity In₂O₃. The elemental analysis of the calcination residue and evaporate is shown in Table 4 below: Table 4
[0040] The elemental analysis results of the residue after calcination are as follows: Figure 9 As shown in (a), the O content at point 1# is 47.16 wt.% and the Al content is 51.51 wt.%, indicating that this area is mainly composed of Al2O3 powder; while points 2# and 3#, although different in morphology, both show that they are reduced In alloys according to elemental analysis.
[0041] The elemental analysis of the metal obtained after reduction of the evaporator is as follows: Figure 9 As shown in (b), the In content at points 4#, 5#, and 6# all exceed 80 wt.%, and also contain small amounts of Sn, O, and C. This indicates that the reduced product is mainly metallic indium, and the residual impurities may originate from incomplete reactions or surface oxidation during the reduction process.
[0042] The point element analysis results of the metal surface shell after the evaporation product was reduced are as follows: Figure 9 As shown in (c). Point 7# consists of dark-colored particles with a high C content of 62.92 wt.%, indicating incompletely consumed activated carbon residue. Point 8# has high Al, In, and O contents, indicating it is a mixed region of Al2O3 and In. Point 9# exhibits a distinct white morphology, and its elemental composition is basically the same as that of point 8#, suggesting it is caused by fragments from the tubular furnace wall. Since the density of Al2O3 is much lower than that of In, these particles easily float on the metal surface; larger particles (such as point 9#) are easily observed under low magnification, while smaller particles (such as point 8#) are not easily identified under low magnification. The elemental analysis of the calcination residue and evaporated material after reduction is shown in Table 5 below: Table 5
[0043] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing an indium-tin alloy, characterized in that the steps include... include: S1. Crush the ITO sputtering material into powder and dry it; S2. Lay the dried ITO sputtering material in a ceramic boat, and control the oxygen partial pressure to 10 under vacuum or protective gas atmosphere. -15 Pa~10 -10 Pa, heat to 1200℃~1300℃ and hold for 2~9 hours; S3. Cool to room temperature, collect the condensed In2O3 and SnO2 powders, add a reducing agent to the In2O3 and SnO2 powders, heat to reduce, and obtain In-Sn alloy.
2. The method for preparing the indium-tin alloy according to claim 1, characterized in that, The pretreatment consists of magnetic separation and manual screening.
3. The method for preparing the indium-tin alloy according to claim 1, characterized in that, The particle size of the powder is no greater than 74 μm.
4. The method for preparing the indium-tin alloy according to claim 1, characterized in that, The drying temperature is 100℃~300℃, and the time is 6-8h.
5. The method for preparing the indium-tin alloy according to claim 1, characterized in that, The thickness of the ITO sputtering material is 0.5-1cm.
6. The method for preparing the indium-tin alloy according to claim 1, characterized in that, The heating process includes: first raising the temperature to 800°C at a heating rate of 10°C / min, and then raising it to 1200~1300°C at a heating rate of 5°C / min.
7. The method for preparing the indium-tin alloy according to claim 1, characterized in that, The reducing agent is carbon.
8. The method for preparing the indium-tin alloy according to claim 1, characterized in that, The amount of reducing agent added is 8-16% of the mass of In2O3 and SnO2 powders.
9. The method for preparing the indium-tin alloy according to claim 1, characterized in that, The reduction temperature is 1000~1300℃, and the reduction time is 2-12h.
10. The method for preparing the indium-tin alloy according to claim 1, characterized in that, The In-Sn alloy also includes vacuum distillation purification.
Citation Information
Patent Citations
A method for preparing indium-tin alloy by high-temperature reduction of waste ITO targets
CN114231743B